Ethyl 2-Succinate-Anthraquinone Attenuates Inflammatory Response and Oxidative Stress via Regulating NLRP3 Signaling Pathway - Feng, Burong; Zhao, Xiuye; Zhao, Wei; Jiang, Huiwei; Ren, Zijing; Chen, Yingfu; Yuan, Ye; Du, Zhimin (Frontiers in Pharmacology, 2021)
Aloe-emodin possesses widely antibacterial, anti-inflammatory, antioxidant, antiviral, and anti-infectious. This study investigated the effect of Ethyl 2-succinate-anthraquinone (Luhui derivative，LHD) on inflammation. In vitro, THP-1 macrophage inflammation model, made by 100 ng/mL phorbol-12-myristate-13-acetate (PMA) and 1 μg/mL LPS for 24 h, was constructed. LHD group (6.25 μmol/L, 12.5 μmol/L, 25 μmol/L, 50 μmol/L) had no effect on THP-1 cell activity, and the expression of IL-6 mRNA was downregulated in a concentration-dependent manner, of which the 25 μmol/L groups had the best inhibitory effect. The migration of THP-1 macrophage with LPS-induced was decreased by LHD. Moreover, LHD suppressed ROS fluorescence expression by inhibiting MDA expression and increasing SOD activity. In vivo, we revealed that LHD, in different doses (6.25 mg/kg, 12.5 mg/kg, 25 mg/kg, 50 mg/kg), has a protective effect on stress physiological responses by assessing the body temperature of mice. Interestingly, acute lung injury (e.g. structure of the alveoli disappeared, capillaries in the alveolar wall are dilated and congested, etc.) and liver damage (e.g. hepatocyte swelling, neutrophil infiltration, and hepatocyte apoptosis) were obviously improved at the same condition. Furthermore, we initially confirmed that the LHD can down-regulated the expression of NLRP3, IL-1β, and caspase-1 protein thereby mediating the NLRP3 inflammasome signaling pathway to produce anti-inflammatory effects. In conclusion, our results indicate that LHD exerts anti-inflammatory via regulating the NLRP3 signaling pathway, inhibition of oxidative stress, and THP-1 macrophage migration.